Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior (OCB) pada Bagian Cleaning Service PT. Gokko Mirai Indonesia - Riska Ristiana; Asep Jamaludin; Nandang (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of job satisfaction and organizational commitment on OCB at PT Gokko Mirai Indonesia, Indonesia. The method used was descriptive quantitative. The sampling method used was saturated sampling, while data were collected by distributing questionnaires to 76 respondents from the cleaning service department, which were then analyzed for partial and simultaneous effects using path analysis, coefficient of determination, and hypothesis testing with t-test and F-test. The results showed that: The effect of job satisfaction on OCB is positive and significant. Hypothesis testing results in a value of t> t-table or (3.786> 1.992) and a probability of 0.000 <0.05, meaning that H1 is accepted, indicating a positive and significant effect of job satisfaction on OCB. The effect of organizational commitment on OCB is positive and significant. Hypothesis testing produces a value of (4,903> 1,992) and a probability of 0.000 <0.05, meaning that H2 is accepted, indicating a positive and significant effect of organizational commitment on OCB. The simultaneous test results of job satisfaction and organizational commitment are positive and significant to OCB. Hypothesis testing results in (82.0502 > 3.12) and a probability of 0.000 < 0.05, then H3 is accepted, indicating a positive and significant effect of job satisfaction and organizational commitment on OCB. Based on the research results, it can be concluded that job satisfaction partially affects OCB at PT Gokko Mirai Indonesia. Organizational commitment affects OCB at PT Gokko Mirai Indonesia, and simultaneously, job satisfaction and organizational commitment affect OCB at PT Gokko Mirai Indonesia.